2015
DOI: 10.1016/j.ijcha.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac calcified amorphous tumor: A systematic review of the literature

Abstract: BackgroundCalcified amorphous tumor (CAT) of the heart is a rare non-neoplastic intracavitary cardiac mass. Several case reports have been published but large series are lacking.ObjectiveTo determine clinical features, current management and outcomes of this rare disease.DesignA systematic review of all articles reporting cases of CAT in order to perform a pooled analysis of its clinical features, management and outcomes.Data sourcesAn electronic search of all English articles using PUBMED was performed. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 29 publications
5
99
1
Order By: Relevance
“…CATs can have a mobile appearance or an immobile one (firmly attached to the ventricle) on gradient-echo cine sequences. Configuration and shapes of cardiac CATs are variable in all published cases and in our study (14). Our results suggest that mass shapes, such as ovoid, irregular, tubular, triangular, and spherical, are nonspecific features for CAT.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…CATs can have a mobile appearance or an immobile one (firmly attached to the ventricle) on gradient-echo cine sequences. Configuration and shapes of cardiac CATs are variable in all published cases and in our study (14). Our results suggest that mass shapes, such as ovoid, irregular, tubular, triangular, and spherical, are nonspecific features for CAT.…”
Section: Discussionsupporting
confidence: 38%
“…De Hemptine et al (14) reported a literature review of 27 articles with 42 cases to provide more insight into the clinical characteristics of this disease. However, these studies did not report the imaging features of CAT.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that denatured serum components were accompanied by calcification with the background of chronic inflammatory changes [1]. Hemptinne and his colleagues reported the clinical features about 42 patients with CAT retrospectively, which said that the mean size of the tumor was 29 × 17 mm, and 36% of CAT occurred in the mitral valve or its annulus, 21% in the right atrium, 17% in the right ventricle [2]. 31% of CAT had valvular disease, 21% had end stage renal failure, 14% had diabetes, and 12% had coronary artery disease as complications.…”
Section: Discussionmentioning
confidence: 99%
“…31% of CAT had valvular disease, 21% had end stage renal failure, 14% had diabetes, and 12% had coronary artery disease as complications. Particularly, patients with CAT developed with the mitral valve annular calcification (MAC) have reported to be closely related to the end stage renal disease with maintenance dialysis [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation